Teaching financial and economic literacy in general education institutions using digital and physical learning resources of universal design - Anushidze, Ana; Beridze, David (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
The theme is based on best practices from European countries, Japan and China in 2020-2023, and the results were presented in the form of three focus groups and a questionnaire that we conducted at national level in 2023-2024, collecting data from various pre-school and secondary schools. It was revealed that the implementation of activities in terms of the basics of arithmetic, financial skills and economic literacy, the understanding of relevant information in general educational institutions is fragmented and does not have a systematic, consistent character, which would ensure the development of thinking skills of each student in the financial and economic direction. Based on the urgency of the issue, general educational institutions need flexible and effective educational projects that ensure the involvement of all students in the educational process, using digital and material resources of appropriate universal design.